Pla Bu Thong, Bawang Merah Bawang Putih: Perbandingan Cerita Rakyat Thailand dan Indonesia - Musfiroh Wajeeismai; Syahrul Ramadhan; Tressyalina Tressyalina; Afnita Afnita (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This article analyzes the folk tales of Pla Bu Thong and Bawang Putih Bawang Merah. These two stories have two countries, namely Thailand and Indonesia, which are located in the Southeast Asia region. These two folk tales were taken from the online library. The two folktales as data sources are compared to see the differences and similarities in these parts. By making a comparison, it was found that there were differences between the three stories in the elements of characters and characterization as well as the way in which the problems they faced were resolved. The existence of parts that show these differences at a further stage shows similarities. Differences in character and characterization are equalized by characters who both have the same temperament and family background. The difference is the location chosen to solve the problem. The differences in several elements that make up literary works lead to the same aims and objectives.